Analyse de l’influence du taux de perfusion sanguine Sur la distribution de Température - DLALI Djamel (My University, 2012)
The transfer of heat in living tissue is a complex process because it implies a combination of thermal conduction in fabrics, the convection and the perfusion of blood. Several mathematical models were developing to describe the transfer of heat in live biological fabrics. These models were largely used in the analysis of hyperthermia, in the treatment of cancer, the surgery with the laser, the cryosurgery, the cry conservation, and of many other applications. The model most largely used in the bioheat was introduced by Pennes in 1948.Pennes with proposed a model simplifies to describe the effect of the blood perfusion on the transfer of heat. In this memory a digital model 3D based on finished differences FDTD developed at the point. This model makes it possible to calculate the distribution of the specific rate of absorption (SAR), the transfer of heat in the body subjected to an electromagnetic field, and shows the influence of rate of perfusion on the transfer of heat.
Keywords: Bioelectromagnetism, SAR (Specific Absorption Rate), FDTD, microwave, hyperthermia, model Pennes, blood perfusion